2007
DOI: 10.1088/0957-0233/18/7/004
|View full text |Cite
|
Sign up to set email alerts
|

Genetic algorithm-based form error evaluation

Abstract: Form error evaluation of geometrical products is a nonlinear optimization problem, for which a solution has been attempted by different methods with some complexity. A genetic algorithm (GA) was developed to deal with the problem, which was proved simple to understand and realize, and its key techniques have been investigated in detail. Firstly, the fitness function of GA was discussed emphatically as a bridge between GA and the concrete problems to be solved. Secondly, the real numbers-based representation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 7 publications
0
21
0
Order By: Relevance
“…This will further help in minimizing the economic loss occurring in manufacturing of the part. The result shows that MPSO algorithm has higher computational accuracy and its optimization result surpassed those from the other methods [3], [8], [29] and from LSM. The iterative curve for PSO and MPSO is shown in Fig.4.a), Fig.4.b) confirming better performance and efficiency of the proposed MPSO algorithm.…”
Section: Practical Examples (Straightness)mentioning
confidence: 95%
See 2 more Smart Citations
“…This will further help in minimizing the economic loss occurring in manufacturing of the part. The result shows that MPSO algorithm has higher computational accuracy and its optimization result surpassed those from the other methods [3], [8], [29] and from LSM. The iterative curve for PSO and MPSO is shown in Fig.4.a), Fig.4.b) confirming better performance and efficiency of the proposed MPSO algorithm.…”
Section: Practical Examples (Straightness)mentioning
confidence: 95%
“…Table 2 shows the results presented in literature [30] along with the solution provided by the proposed MPSO algorithm. For example 1, it is observed that minimum zone straightness error obtained by LSM is 0.0017, Optimization Technique Zone (OTZ) [8] is 0.0017, Linear Approximation Technique (LAT) [8] is 0.0017, GA [3] is 0.001672, and PSO [29] is 0.001711, while the minimum zone straightness error obtained by the proposed MPSO is 0.00160. If the allowable straightness tolerance is 0.00165 inch, all the algorithms except the MPSO algorithm overestimate the tolerances and hence result in rejection of good parts.…”
Section: Practical Examples (Straightness)mentioning
confidence: 99%
See 1 more Smart Citation
“…In the field of Agricultural, water conservancy, weather and economy, some error factors are used to evaluate the error, such as average absolute error, relative error [12][13][14][15]. But these quality factors haven't been used systematically and adaptively to evaluate an age recognition system.…”
Section: Related Workmentioning
confidence: 99%
“…Earlier, coordinate measuring machines (CMMs) are used for acquiring 3D cloud points and for performing o®line/ online inspection activities. [2][3][4] But nowadays, use of noncontact 3D scanner is increasing for CAD modeling, drawing of physical components and part inspection purposes. [5][6][7] The laser-scanning technology has an inbuilt capacity to capture the pro¯le of a component, and therefore, has received considerable appreciation in the industry.…”
Section: Introductionmentioning
confidence: 99%